Ceremonial Execution and Public Rewards : Some Historical Scenes on New Kingdom Private Stelae - Schulman, Alan R. (1988)
The repertoire of scenes on Egyptian private stelae is relatively limited to scenes of the funerary banquet, of the deceased receiving offerings, or making them. About the reign of Thutmose IV in the New Kingdom, and lasting through the end of Dynasty 20, scenes which seemingly have nothing to do with these motifs begin to occasionally appear in the stelae repertoire: the king smiting his enemies, receiving a weapon from a god, a god’s barque carried in procession, the deceased being rewarded with gold collars or riding in his chariot, and the like. The present work attempts to discern why such scenes appear on private stelae. After a careful examination of all of the known private monuments of this class which depict who specific motifs, a) the king smiting an enemy and b) the awarding of gold sbiw-collars to the stela’s dedicatee, a total of approximately 35 monuments, the conclusion was reached that such representations are not merely timeless stereotypes but actually represented specific events which took place at specific points in time. Thus the stelae function on two levels simultaneously, a concrete one commemorating the original event, and an abstract one in which the scene illustrated is repeated for eternity.